Halitosis: a conceptual, etiologic and therapeutic approach - Viana, Karolina Skarlet Silva; Souza, Esther Aranda Figueiredo; Lima, Rafael Paschoal Esteves; Cota , Luis Otavio Miranda (Brazilian Dental Science, 2024)
Objective: Halitosis is the offensive odor emanated by the oral and nasal cavities and perceived by the individual and/or by other people. Halitosis is a symptom that directly impacts on the social aspects of an individual’s life and may be a sign for a systemic disorder in some cases. Material and Methods: A search was conducted on the literature in order to gather the main aspects about halitosis and make a review about the main features necessary to the clinical practice when a professional deals with a patient with halitosis. Results: The information was summarized and discussed with a focus on what clinicians should be aware of when dealing with a patient with halitosis. Conclusion: Halitosis is a prevalent symptom that affects approximately 25% of the individuals. Its classification takes into consideration the origin of the compounds producing the malodor. The diagnosis must take into consideration the various etiological possibilities before defining the treatment. The treatment must be focused on the cause and since there is a wide range of possible causes, halitosis needs a multidisciplinary approach. KEYWORDS Dimethyl sulfide; Halitosis; Hydrogen sulfide; Odorants; Oral hygiene.